2021
DOI: 10.3390/molecules26071973
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Antioxidant Activity of Spray-Dry Broccoli (Brassica oleracea var Italica) Stalk and Floret Juice Powders

Abstract: This research presents the microencapsulation and conservation of antioxidants of broccoli juice processed by spray drying, and proposes the use of a by-product as a technological application. Broccoli juice (BJ) extracted from two sources, stalks and florets, was spray-dried employing maltodextrin (MX) as a carrier agent at concentrations of 5, 7.5, and 10%, and inlet temperatures of 150 and 220 °C. The total phenolic content (TPC), and antioxidant activity (AA) of the BJ-MX powders were determined together w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
2
16
1
Order By: Relevance
“…According to Gonçalves et al [18], catechins and procyanidins were the flavan-3-ols found in sweet cherry fruits. Their presence has already been reported in other studies [6,11,55]. Furthermore, procyanidins were identified in sweet cherry fruits from different cultivars (values ranging from 6.2 to 290.6 µg/g dw), representing less than 18% of the total non-colored phenolics [18].…”
Section: Flavan-3-olssupporting
confidence: 69%
“…According to Gonçalves et al [18], catechins and procyanidins were the flavan-3-ols found in sweet cherry fruits. Their presence has already been reported in other studies [6,11,55]. Furthermore, procyanidins were identified in sweet cherry fruits from different cultivars (values ranging from 6.2 to 290.6 µg/g dw), representing less than 18% of the total non-colored phenolics [18].…”
Section: Flavan-3-olssupporting
confidence: 69%
“…In addition, ITCs have been recognized as potential candidates for new antimicrobial compounds with a broad spectrum of activity due to their ability of reducing oxygen consumption and depolarizing the mitochondrial membrane in bacterial cells [ 13 ]. Due to the featured medicinal advantages of broccoli florets, their consumption has increased over 940% over the last 35 years [ 14 ]. In fact, global production of broccoli and cauliflower has increased by about 6 million ton in the last 10 years, with approximately 26.92 million ton produced in 2019 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The extraction was conducted under constant stirring for 1 h. After this period, the extracts were centrifuged for 15 min at 11,000 rpm and 4 °C; the supernatant was filtered and stored at 4 °C in amber bottles to protect them from light damage. Next, the precipitate was re-suspended in a methanol solution (70%) and stirred for 1 h, and the extracts were centrifuged, filtered, and mixed with the previous supernatant [ 10 ]. Extracts were prepared in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…These observations suggested that the powder microstructure was better conserved at the intermediate and highest MX concentration. Saavedra-Leos et al 2021 and Araujo-Díaz et al 2017 indicated that agglomerated structures are related to a collapse of the microstructure during spray drying [10,15]. Przybył et al 2018 reported the morphology of strawberry powders-with different quality, the bad batches presented large particle sizes and conglomeration of particles, while the good batches were presented as spherical with deflated shape [37].…”
Section: Microstructural Analysismentioning
confidence: 99%
See 1 more Smart Citation